Pengaruh Senam Otak Terhadap Peningkatan Fungsi Kognitif Pada Lansia - Yanuri Sudarsono; Istiqomah; E. Iswantiningsih (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Background: Older people over 60 years of age suffer a deacline in cognitive function in the brain because of a deterioration in the function of nervous system that hinders thinking, concentration and communication. The number of incidents decline in cognitive function in 2020 reached 26,26 million and increased by > 10% reaching 48,2 million by 2035 and 2050 to 131,5 million. Efforts to increase cognitive function in older age include brain calisthenics, which the brain exercise are able to release blood and oxygen flow to the brain and stimulate the brain to work in the 3 dimensions of lateralis, focus and centrality. Purpose: The Literature review is intended to analyze the effects of brain exercise on improving cognitive function in the elderly. Method: A study of literature analyzing 165 journals through Google Scholar and Research Gate searches with key words For brain exercise, cognitive function, and advanced age with a ten years launch period (2010 – 2020). The right to be held in the right will be held in the right. Results: The 5 journal review prior to elderly brain exercise most experienced mild cognitive impairment (17-23) after brain exercise developed an increased cognitive function to no cognitive impairment (24-30), Ho was rejected and Ha was accepted with a statistical test score p value < 0,05. Conclusion: Results from the 5 journal review obtained results from statistics p value < 0,05, which suggest that brain brain exercise on improving cognitive function in the elderly.